Second Harmonic Generation under Strong Influence of Dispersion and Cubic Nonlinearity Effects - Mironov, Sergey; Lozhkarev, Vladimir; Ginzburg, Vladislav; Yakovlev, Ivan; Luchinin, Grigory; Khazanov, Efim; Sergeev, Alexander; Mourou, Gerard (IntechOpen, 2010)
None